C-reactive protein and Platelets changes in preterm neonates with patent Ductus Arteriosus - Mohammad Mahdi Bagheri; Homa Ghabeli; Pedram Niknafs; Saeedeh Parvaresh (Journal of Kerman University of Medical Sciences, 2019)
Introduction: This study aimed to investigate CRP and platelet count changes in preterm neonates with Patent Ductus Arteriosus on the seventh day of birth compared to the third day. Methods: This longitudinal study was conducted on fifty neonates with PDA complications in Afzalipour hospital in 2017-2018. All neonates underwent repeated echocardiography before the closure of their arterial duct and 2 cc of blood sample was taken from each neonate and was sent to the laboratory for platelet and CRP count test. Result: The mean of platelet was 296.17±18.08 on day 7, and it was significantly different compared to day 3 (195.49 ± 10.49). The arterial ducts of 15 neonates out of 50 patients with PDA were closed on the seventh day. The mean of CRP was significantly different in neonates with PDA (35.70) compared to neonates with closed arterial ducts (2.32) on day 7. Conclusions: The results of this study revealed that PDA is associated with a low number of platelets and high level of CRP in preterm neonates.